2019
DOI: 10.1002/jcad.12289
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Life Balance and Work Addiction in High‐Pressure, High‐Demand Careers

Abstract: Life balance is indicative of creating and sustaining a meaningful and satisfying quality of living. Contrarily, work addiction is overinvesting in work‐related behaviors, thereby truncating important life‐balance domains. Given a growing body of literature specific to life balance and the increasing incidence of work addiction and burnout among professionals, the authors evaluated life balance and work addiction among 409 professionals in high‐pressure, high‐demand careers. A strong relationship between life‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The study findings indicate that entrepreneurs who endorse higher levels of work addiction experience higher levels of anxiety, substance use, higher levels of negative mood and perceptions of the future, sleep disturbances, and compromised relationships with friends. These findings support previous research (Reiner et al., 2019), indicating work addict professionals in high‐pressure, high‐demand careers have a poor life balance. Thus, this study's results indicate that entrepreneurs high on neuroticism are more likely to experience work addiction, higher anxiety levels, and poor life balance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study findings indicate that entrepreneurs who endorse higher levels of work addiction experience higher levels of anxiety, substance use, higher levels of negative mood and perceptions of the future, sleep disturbances, and compromised relationships with friends. These findings support previous research (Reiner et al., 2019), indicating work addict professionals in high‐pressure, high‐demand careers have a poor life balance. Thus, this study's results indicate that entrepreneurs high on neuroticism are more likely to experience work addiction, higher anxiety levels, and poor life balance.…”
Section: Discussionsupporting
confidence: 91%
“…Essential domains of life balance are related to optimism, relationships, stress/anxiety, career satisfaction, and health (Davis et al, 2014). Reiner et al (2019) evaluated life balance of professionals in high-pressure, high-demand careers. Researchers indicated that work addicts experience more stress/anxiety, sleep disturbances, lower scores on relationship areas (such as sex/intimacy, quality of relationships, friendship), and dissatisfaction with their careers, thus reducing life balance perceptions.…”
Section: Life Balance and Work Addictionmentioning
confidence: 99%
“…Counselors, through discussion or assessment of WLB, may move their clients to consider the nexus of work and life domains, the impact of the decisions they make, and the consequences of being devoid of balance in their lives. Counselors engaging with clients seeking to better balance their lives should be prepared to assess indicators of work addiction and support clients as they restructure their lives (Reiner et al, 2019). Counselors may also assist clients by guiding them on how to advocate within the work setting for the creation of a healthy work environment that support not only clients' WLB but also their performance in the organizations for which they work.…”
Section: Discussionmentioning
confidence: 99%
“…Studies consistently show that WA is associated with low sleep quality and sleep problems (see Griffiths et al, 2018). Recently, there has been a rapidly increasing number of studies aiming to explain the mechanisms by which WA affects sleep disturbance (Gillet, Morin, Sandrin, & Houle, 2018;Hancock et al, 2019;Reiner et al, 2019;Scafuri et al, 2019;Spagnoli, Balducci, Fabbri, Molinaro, & Barbato, 2019;Spagnoli, Balducci, Scafuri, Maiorano, & Buono, 2018). This is an especially appreciated effort since sleep is closely related to health and mortality (Gallicchio & Kalesan, 2009).…”
Section: Work Addiction Eating Disorders and Sleepmentioning
confidence: 99%